Relationships of Pitcher Plants (Nepenthes spp.) in Kapusin Nature Conservation Area, Pontianak, West Borneo - Oktapia, Ersa; Turnip, Masnur; Lovadi, Irwan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Pitcher plants (Nepenthes spp.) are supporting ecotourism activities plants because it has a unique morphologies. The Kapusin Nature Conservation Forest is a secondary forest that has potential as an ecotourism site because of its beauty and also the natural habitat of Nepenthes spp. This research aims to determine the types and relationships of Nepenthes spp. sin the Kapusin Nature Conservation Area. Sampling used the exploring method and then the results were identified by observing the morphologies of the stems, leaves and pitchers. There were 49 morphological characters observed, consisting of 29 qualitative characters and 20 quantitative characters. Relationships between individuals was cluster analyzed using the UPGMA (Unweighted Pair-Group Method with Arithmatic) method using NTSys (Numerical Taxonomy System) software version 2.02. The results obtained were 4 Nepenthes and 2 hybrid Nepenthes consisting of N. ampullaria, N. bicalcarata, N. mirabilis, N. gracilis, N. xtrichocarpa and N. xcoccines. The results of the grouping analysis showed that the Nepenthes found had a similarity rate of 53% and were divided into 4 clusters, namely cluster 1 consisting of N. ampullaria and N. xtrichocarpa species, cluster 2 of N. gracilis species, cluster 3 of N. mirabilis and N. xcoccines species. and cluster 4 species of N. bicalcarata.